2012
DOI: 10.1007/s11434-012-5439-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of nucleotide excision repair by arsenic

Abstract: Inhibition of DNA repair is one proposed mechanism for the co-mutagenicity/co-carcinogenicity of arsenic. This review summarizes the current literature on the effects of arsenic compounds on nucleotide excision repair (NER). Several possible mechanisms for the observed NER inhibition have been proposed. Modulation of the expression of NER proteins has been considered to be one possibility of impairing the NER process. However, data on the effects of arsenic on the expression of NER proteins remain inconsistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…115117 These trivalent arsenicals were found to inhibit the activities of several DNA repair proteins, including poly(ADP-ribose) polymerase-1 (PARP-1), formamidopyrimidine-DNA glycosylase (Fpg), and xeroderma pigmentosum group A protein (XPA), each containing a zinc finger DNA binding domain. 118,119 The interactions between these repair proteins and arsenic compounds resulted in the release of zinc.…”
Section: Chemical Basis and Biological Implications Of Arsenic Bindinmentioning
confidence: 99%
“…115117 These trivalent arsenicals were found to inhibit the activities of several DNA repair proteins, including poly(ADP-ribose) polymerase-1 (PARP-1), formamidopyrimidine-DNA glycosylase (Fpg), and xeroderma pigmentosum group A protein (XPA), each containing a zinc finger DNA binding domain. 118,119 The interactions between these repair proteins and arsenic compounds resulted in the release of zinc.…”
Section: Chemical Basis and Biological Implications Of Arsenic Bindinmentioning
confidence: 99%
“…The possible mechanisms of NER inhibition by As include its effects on the expression of NER protein, the function of NER protein, the p53 phosphorylation, and p53 DNA‐binding activity, which could modulate NER via transcriptional activation of downstream NER genes . Several studies demonstrated that excision repair cross‐complementing proteins 1 and 2 (ERCC1 and ERCC2), as two of the key components of the NER pathway, are regulated by As .…”
Section: Mechanisms Of Ddr/repair In Cancer: Trace Elements Implicationmentioning
confidence: 99%
“…255 The possible mechanisms of NER inhibition by As include its effects on the expression of NER protein, the function of NER protein, the p53 phosphorylation, and p53 DNA-binding activity, which could modulate NER via transcriptional activation of downstream NER genes. 256 Several studies demonstrated that excision repair crosscomplementing proteins 1 and 2 (ERCC1 and ERCC2), as two of the key components of the NER pathway, are regulated by As. 257,258 Exposure to As can decrease expression levels of Lig1 and Lig3 at both mRNA and protein levels in mammalian cells, expression levels of ERCC1, XPF, and XPB in lymphocytes, and expression of ERCC1 at both mRNA and protein levels in human and cultured cardiomyocytes.…”
Section: As Implicationmentioning
confidence: 99%
“…Emerging evidence suggests that inactivation of this enzyme causes the disruption of energy homeostasis (Shen et al, 2013a) and possibly iron homeostasis (Ye and Rouault, 2010). DNA repair enzymes that mediate nucleotide excision repair (NER) can also be inhibited by As through several pathways, including the induction of nitric oxide (NO) (Shen et al, 2013b). It is considered that NO interacts with the iron center of IRPs, and thus alters the ferritin and transferrin levels, resulting in enlarged cellular LIP (Verma et al, 2015).…”
Section: Arsenic (As)mentioning
confidence: 99%